2-Methoxyethanol: harmonic tricks, anharmonic challenges and chirality-sensitive chain aggregation. Issue 27 (6th July 2020) - Gawrilow, Maxim; Suhm, Martin A.
Abstract : Simple mass-scaling of the torsional proton in 2-methoxyethanol emulates strong mixing with a skeletal motion observed in experiment. Abstract : The Raman spectrum of jet-cooled, nearly monoconformational 2-methoxyethanol reveals a strong, aggregation-sensitive resonance in the backbone stretching region and pronounced chirality-dependent dimerisation effects in the OH stretching region. These effects are disentangled by a dual-detection scheme which simultaneously probes the two spectral regions. The performance of mass-scaled harmonic wavenumber predictions and of vibrational perturbation theory in reproducing these spectral features is explored.